The efficacy of vitamin D3 supplementation in controlling insulin resistance among individuals with obesity - منهل نبيل يوسف (Latakia University Journal -Medical Sciences Series, 2022)
Background: Obesity is associated with increased risk of insulin resistance and type 2 diabetes. Evidence suggests that vitamin D deficiency may exacerbate these metabolic disorders. This study aimed to evaluate the effect of vitamin D3 supplementation on insulin resistance among obese adults. Methods: A randomized, placebo-controlled, single-blind clinical trial was conducted involving 24 participants (12 intervention, 12 placebo) with obesity (BMI > 30 kg/m²), confirmed vitamin D deficiency, and insulin resistance (HOMA-IR > 2.0). The intervention group received vitamin D3 supplements at a dose of 2,000 IU daily for six months, while the placebo group received identical capsules. Metabolic parameters (HOMA-IR, fasting insulin, HbA1c, and 25(OH)D), as well as body weight and waist circumference, were assessed at baseline, 3 months, and 6 months. Data were analyzed using T-tests and repeated measures ANOVA, with significance set at P < 0.05. Results: HOMA-IR decreased in the vitamin D3 group from 4.09 ± 0.82 to 3.19 ± 0.70 (P = 0.002), fasting insulin from 18.4 ± 3.2 to 14.9 ± 2.8 µU/mL (P = 0.001), and HbA1c by 0.5% (P = 0.003), while 25(OH)D levels increased from 15.2 ± 3.5 to 32.6 ± 4.1 ng/mL (P < 0.001). No significant changes were observed in the placebo group. The intervention group also showed modest reductions in weight (-3.0 ± 1.2 kg) and waist circumference (-2.6 ± 1.0 cm). No serious adverse events were reported, and adherence was high (93%). Conclusion: Vitamin D3 supplementation over six months led to significant improvements in insulin resistance among obese adults with vitamin D deficiency, even in the presence of only minimal weight loss. These findings highlight the potential role of vitamin D3 in modulating metabolic and inflammatory pathways related to insulin sensitivity. Routine assessment and correction of vitamin D deficiency should be considered in obesity management programs, and further large-scale studies are needed to confirm these results.